IL-17 cytokine family and receptors - Dong, Chen; Chang, Seon Hee (Henry Stewart Talks, 2012)
IL-17 cytokine, Sequence homology, Cellular sources, Receptor usage-signaling adaptor and pathways, Biological target cells, Function in autoimmune disease and infection